رؤية مستقبلية لقطاع النقل البحري مع دراسة شركتي ايفرجين ويومينخ - سائر صليبا (Tishreen University, 2018)
تمتاز صناعة النقل البحري بأنها صناعة دولية تتشابك فيها و تتداخل الشركات الملاحية الدولية بهدف المنافسة على نقل التجارة الدولية بحرا ً وأهم ما يميز هذه الصناعة كثافة رأس المال اللازم للاستثمار فيها إن كان في شراء السفن أو تشغيلها أو استئجارها في الموانئ والمحطات و ترسانات البناء والصيانة و الإصلاح . لقد كان التطور سريعا ً والتقدم التقني في هذا المجال خلال السنوات الأخيرة من القرن الماضي ومع بداية القرن الحالي. وظهر هذا التطور جليا ً في ظهور الاشكال المختلفة ذات التخصص الكبير للسفن إضافة إلى الأنظمة الحديثة و المتطورة في عمليات تداول ومناولة البضائع في المرافئ وعلى السفن، كذلك في أنظمة الاتصال و المراقبة و السلامة المتبعة من قبل أكبر الشركات الملاحية العالمية، وكل ذلك يهدف في النهاية إلى تقديم خدمة أفضل وبزمن أقل وتكلفة مقبولة من قبل جميع أطراف النشاط الملاحي ( مالك البضاعة - المشتري - الوكيل - الشاحن وغيرهم ). لوحظ في السنوات الأخيرة تطورا ً نوعيا ً في بناء السفن نوعا ً وحجما ً، وقد ارتبط ذلك بشكل وثيق بمصادر وموارد التمويل وبالحصول على راس المال اللازم وقد تنوعت هذه المصادر وبنية الطرق التقليدية المتمثلة بالقروض البنكية بأنواعها والطرق الغير تقليدية كالتأجير التمويلي أو التأجير بهدف الشراء. Characterized by the shipping industry as an international industry intertwined with and international shipping companies overlap in order to compete on international trade, transport by sea and the most important characteristic of this industry the necessary capital to invest in intensity if the purchase of ships or operated or rented in ports and terminals, and the arsenals of construction, maintenance and reform. It was a rapid development of technical progress in this area during the last years of the last century with the beginning of the current century. This is evident evolution and appeared in the emergence of various forms of large specialization of ships as well as modern and advanced systems in handling and cargo handling operations in ports and on ships, as well as in communication systems and surveillance and safety adopted by the world's largest shipping companies, all of which is aimed at the end to provide a better service and a time of lower cost accepted by all parties to the shipping activity (owner of the goods - the buyer - the agent - the charger and others). Observed in recent years, a remarkable development in the construction of some kind and size of vessels, and this has been associated closely sources and sources of financing and access to capital needed was these sources varied and the structure of the traditional practice of bank loans all kinds of roads and roads unconventional Lease Kaltoger or leasing in order to purchase